1974
DOI: 10.1029/jb079i020p03019
|View full text |Cite
|
Sign up to set email alerts
|

Experiments with maximum entropy power spectra of sinusoids

Abstract: Burg's maximum entropy technique is applied to the estimation of power spectra of short sinusoids. The estimated spectral maximum was found to shift in relation to the true maximum. The frequency shifts depend upon the initial phase and the length of the sinusoid. The influence of the number of terms in the prediction error filter, the number of the data samples, and the noise intensity are also considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(59 citation statements)
references
References 4 publications
2
57
0
Order By: Relevance
“…According to Chen and Stegen (1974), the MEM gives a reasonably good spectrum for data length that covers more than a full cycle of a sinusoid. Ulrych (1972) showed that the sharp spectral peak was given from the data containing only 57% of a cycle of a sinusoid.…”
Section: Data and Methods Of Analysismentioning
confidence: 99%
“…According to Chen and Stegen (1974), the MEM gives a reasonably good spectrum for data length that covers more than a full cycle of a sinusoid. Ulrych (1972) showed that the sharp spectral peak was given from the data containing only 57% of a cycle of a sinusoid.…”
Section: Data and Methods Of Analysismentioning
confidence: 99%
“…On the other hand, the frequency at which the MEM spectrum for the truncated sinusoid has maximum oscillates between 0 and 1.84 times the frequency of the sinusoids for all possible initial phases when the truncation length of data is nearly equal to a quater times the period of the sinusoids (Ulrych, 1972 andChen andStegen, 1974).…”
Section: Effect Of the Length Of Prediction Error Filtermentioning
confidence: 99%
“…When using MESA, the spectral resolution is greatly influenced by the number of terms or order of the prediction error filter (PEF); consequently, it is important to determine and use the correct PEF order (Chen and Stegen, 1974). A PEF order that is too small results in a highly smoothed spectrum where some peaks may not be resolved, thus precluding the advantages of MESA.…”
Section: Champ Datamentioning
confidence: 99%